The investigation of the NH3-SCR performance of a copper-based AEI-CHA intergrown zeolite catalyst - Ye, Hongling; Ren, Kai; Wang, Pengfei; Wang, Lin (Frontiers in Chemistry, 2022)
In this work, the ISAPO-34/SAPO-18 intergrown zeolite was prepared by using Phosphate organoamine as the structure guiding agent. The physical-chemical characterizations by XRD, SEM, TG and BET showed that the SAPO-34/SAPO-18 presents a cross-stacked cubic block-like microscopic morphology, with characteristic diffusive diffraction peaks at 2θ=16−18° and 30−33°, with the specific surface area of 557 m2·g−1. Based on the series of copper-based catalysts prepared from SAPO-34/SAPO-18, it was found that the active temperature window shifted to the low temperature with the increase of copper content, and the Brønsted acid site decreased significantly due to copper ion exchange and the zeolite structure framework damage. Among them, the 1.2 wt% sample possesses the widest active temperature window, and the T90 range is 175−435 ℃. After the low-temperature hydrothermal aging treatment, the zeolite structure was eroded, and the catalyst activity was significantly deteriorated.